2005
DOI: 10.1081/jdi-200048236
|View full text |Cite
|
Sign up to set email alerts
|

Silent Myocardial Ischemia and High-Grade Ventricular Arrhythmias in Patients on Maintenance Hemodialysis

Abstract: The occurrence of silent myocardial ischemia (SMI) and serious arrhythmias during hemodialysis (HD) has been well documented. However, it is unclear whether these changes are due to epicardial coronary artery disease (CAD). We conducted a prospective study to assess whether SMI and arrhythmias during HD correlated with angiographically demonstrable CAD. Twenty-three patients with end-stage renal disease on maintenance HD underwent 48-hour Holter monitoring, beginning 24 hours prior to a HD session. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
(12 reference statements)
0
21
0
Order By: Relevance
“…Silent myocardial ischemia, defined by asymptomatic dynamic ST-T changes suggestive of ischemia, has been repeatedly reported with a prevalence of 16–60% (68–72) . Interestingly, studies where coronary angiograms were performed found no correlation between silent ischemia and angiographic findings (69, 72) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silent myocardial ischemia, defined by asymptomatic dynamic ST-T changes suggestive of ischemia, has been repeatedly reported with a prevalence of 16–60% (68–72) . Interestingly, studies where coronary angiograms were performed found no correlation between silent ischemia and angiographic findings (69, 72) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies where coronary angiograms were performed found no correlation between silent ischemia and angiographic findings (69, 72) . This may be explained by the existence of microcirculatory changes in the coronary system in ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ECG has lower sensitivity for ischaemia diagnosis in this patient group [30]. Silent ischaemia and chest pain with unobstructed coronary arteries are common in renal failure [6,30,31]. Cardiac symptoms are thus less reliable for ischaemia diagnosis.…”
Section: Markers Of Ischaemia In Esrdmentioning
confidence: 95%
“…The evidence of HD-induced myocardial ischemia came from electrocardiogram-based studies and isotopic perfusion imaging. Zuber et al demonstrated silent ST-depression occurring during hemodialysis [21] and its rates varied between 15 to 40% in next studies [22][23][24]. Singh et al observed the dialysis-induced myocardial perfusion defects in seven of ten patients, examined by single-photon emission computed tomography [25].…”
Section: Discussionmentioning
confidence: 99%